ANALISIS MULTIREPRESENTASI MAHASISWA PGSD PADA KONSEP GELOMBANG DAN BUNYI - Siti Fatimah (Universitas PGRI Madiun, 2016)
Waves and sound are included in physics subjects material that contains many graphics and mathematical equations. Hence, students need an effective way to understand it in the form of representation. One of the representation main functions is guiding the student to achieve an in-depth understanding. A research was about an analysis of the undergraduate student's multiple representation ability on the material of sound and waves has been conducted. This research involved 148 students from PGSD study program. The results indicated that students have good representation abilities in verbal mode only, while the mathematical and visual representations are needed to be developed.Keywords: Multiple Representation, Waves and Sound.